How far has research into disruptive innovations in the field of sustainability come to date? - Ahmadov, Tarlan; Durst, Susanne; Eriksson, Taina; Jussila, Maria; Saaristo, Aino (Elsevier, 2025)
The term ‘disruptive innovation’ has been on everyone's lips for some years now, both in theory and in practice. This type of innovation is considered promising when it comes to the transition to sustainability. Based on a critical literature review comprising 121 academic articles, this study provides a systematic overview of the state of research on disruptive innovation for sustainability over 20 years. This overview makes it possible to determine whether and how an accumulation of knowledge has taken place in this area. The study reports on the selected theories, methods and definitions of the core concepts used. A thematic analysis was conducted that identified five broad themes, namely business models, people skills, supply chains, product/service development and transformations/transitions. In addition, the evolution of thematic areas over time is presented. The results indicate that there is a significant need for greater knowledge accumulation. This paper proposes concrete directions for future research to come closer to this goal.